2022
DOI: 10.31557/apjcp.2022.23.7.2491
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical Expression of Programmed Death Ligand 1(PDL1) in Endometrial Carcinoma and Its Relation to CD4 and CD8 Positive Immune Cells

Abstract: Objectives: Endometrial cancer (EC) is the most common cancer of the female genital tract. Egypt showed a significant increase in incidence lately of which 25% were premenopausal. Advanced or recurrent disease are mostly unresectable and the traditional adjuvant therapy give modest results with devastating side effects. Late discoveries of immune checkpoint inhibitors have produced promising results. Programmed cell death 1 (PD1) is an immune inhibiting receptor on surface of lymphocytes, which plays critical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…The CD4 +/CD8+ ratio was higher in low-grade specimens, suggesting that CD4 + and CD4 +/CD8+ ratio are independent prognostic factors in OSCC [ 32 ]. Salama et al [ 33 ] investigated the correlation between PDL1 expression and clinicopathological parameters in endometrial cancer (EC) cases, focusing on CD4 and CD8 immune cells. They found that PDL1 was expressed in tumor cells in 67% of cases and in immune cells in 61% of cases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The CD4 +/CD8+ ratio was higher in low-grade specimens, suggesting that CD4 + and CD4 +/CD8+ ratio are independent prognostic factors in OSCC [ 32 ]. Salama et al [ 33 ] investigated the correlation between PDL1 expression and clinicopathological parameters in endometrial cancer (EC) cases, focusing on CD4 and CD8 immune cells. They found that PDL1 was expressed in tumor cells in 67% of cases and in immune cells in 61% of cases.…”
Section: Discussionmentioning
confidence: 99%
“…Significant correlations were observed between PDL1 expression and patient age, LVSI, TILS score, and CD4 +/CD8+ expression. The findings suggest that these variables may serve as predictive biomarkers for successful immune therapy in EC [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…In human hepatocellular carcinoma (HCC) specimens, expression of FXR is markedly decreased in comparison with the level in normal liver (van den Esschert et al, 2011). A recent immunohistochemical analysis on 17 primary HCC cases and 21 non-neoplastic hepatic lesions (i.e., FNH, regenerative nodules, and dysplastic nodules) revealed that FXR expression level was lower in HCC than in non-neoplastic lesions (Salama et al, 2023). The expression and activation of FXR in HCA and its potential role in the malignant transformation of HCA into HCC has not yet been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Liver's X receptors, and have inhibiting LXR activity has been observed to curb cell proliferation and enhance responsiveness to chemotherapy. (Salama et al, 2023;Srivastava et al, 2020).…”
mentioning
confidence: 99%